Preliminary experimental investigations into an oversized coaxial relativistic klystron amplifier at Ka band - Li S.; Duan Z.; Huang H.; Basu B.N.; Dang Z.; Bai Y.; Wang Z.; Gong Y. (My University, 2025)
Preliminary experimental results on an oversized high-power coaxial relativistic klystron amplifier (OCRKA) at Ka band were presented. The measured values on the cold-test setup agreed with those predicted by simulation. An annular intense relativistic electron beam (IREB) was produced by an explosive emission cathode in a diode with beam transmission greater than 88%. The device output power of 100 kW was demonstrated, using a 517 \mathrm{kV}, 4.9\mathrm{kA} IREB. Larger output power could have been obtained with improved input coupler of lower values of insertion loss. © 2019 IEEE.